Potential Health Risks From Mercury (Hg) Exposure Through Rice Consumption In The Sijunjung Gold Mining Area, West Sumatera: - - Randy Novirsa; Aldifa Taufiqurrahman; Septia Pristi Rahmah; Fadilla Azmi (Jurnal Keselamatan Kesehatan Kerja dan Lingkungan, 2026)
Accumulation of mercury (Hg) in food crops can pose serious health risks to humans. In Indonesia, the population may be exposed to mercury through rice consumption, a staple food cultivated in areas surrounding gold mining sites. This study aimed to estimate the health risk associated with mercury exposure through rice consumption among communities living near gold mining areas in Sijunjung Regency, West Sumatra, Indonesia. The study was conducted in artisanal and small-scale gold mining (ASGM) areas using a public health risk assessment approach, determining the risk quotient (RQ) by comparing estimated daily intake (EDI) with the reference dose (RfD) to evaluate real-time and lifetime risk levels. Rice (n = 6) and water (n = 6) samples were collected from paddy fields located near the mining areas, along with one market rice sample (n = 1) as a comparison. A total of 103 adult respondents were included in this study. Data were collected through structured interviews using a standardized questionnaire that assessed consumption habits and lifestyle patterns, including body weight. The results showed that the mean total mercury (T-Hg) concentration in rice from ASGM areas ranged from 0.0087 to 0.01 mg/kg. Exposure assessment indicated that the community was exposed to mercury at levels of 0.053 to 0.23 ug/kg/day through rice consumption. The risk quotient (RQ) values indicated a relatively low risk level based on the analyzed rice consumption pathway. In conclusion, mercury intake from rice consumption in communities around gold mining areas in Sijunjung Regency remains within a tolerable daily intake level. However, potential exposure through other pathways, such as inhalation and consumption of other food sources, warrants further investigation.